Access over 20 million homework & study documents
search

2( 3y)^0Solution if you have power of 0, th

Content type

User Generated

Rating

Showing Page:
1/1
-2(-3y)^0
Solution
if you have power of 0, that becomes 1
hence, -2(-3y)^0 ==> -2(1) = -2 answer

Sign up to view the full document!

lock_open Sign Up

Unformatted Attachment Preview

-2(-3y)^0 Solution if you have power of 0, that becomes 1 hence, -2(-3y)^0 ==> -2(1) = -2 answer Name: Description: ...
Purchase document to see full attachment
User generated content is uploaded by users for the purposes of learning and should be used following Studypool's honor code & terms of service.

Anonymous
This is great! Exactly what I wanted.

Studypool
4.7
Trustpilot
4.5
Sitejabber
4.4